Effect Of Static Stretching Followed By Contrast Water Therapy Recovery On Lactate-dehydrogenase Concentration After Simulated High Intensity Exercise In Youth Soccer Players - Nadir, Hedroug; Mezroua, Said (Journal of Sport Science Technology and Physical Activities, 2025)
The study aimed to know the effect of static stretching followed by contrast water therapy on Lactate-dehydrogenase LDH after simulated high intensity exercise in youth soccer players, the study included 20 players of ESS team U19 category from first professional Algerian championship, the players were randomly divided on two groups 10 players per group (experimental and control ), the experimental group execute static stretching SS followed by contrast water therapy CWT , whether the control group had no activity, the players simulated yoyo test L1 the blood sample was taken, before, after 1h and after 48h to know the concentration of (LDH) in the blood and the rate of recovery. The results of this study showed that static stretching followed by contrast water immersion recovery beneficial to improve the rate of recovery by decreasing LDH concentration and reducing muscle damage after simulated high intensity exercise in youth soccer players.